Temperature dependence of flexoelectric coefficient for bulk polymer polyvinylidene fluoride. (17th December 2018) - Lu, Jianfeng; Liang, Xu; Yu, Wenshan; Hu, Shuling; Shen, Shengping
Abstract: The flexoelectric effect refers to linear coupling between the electric polarization in response to an elastic strain gradient. Despite the extensive study of the flexoelectric effect in ceramics and polymers, knowledge of the temperature dependence of the flexoelectric effect is still lacking. In this work, we experimentally investigate the temperature dependence of the flexoelectric coefficient of bulk polyvinylidene fluoride (PVDF) and analyze the variation of the dielectric constant and flexoelectric coefficient with increasing the temperature. The flexoelectric coefficient for bulk PVDF is found to be increased by ~69% when the temperature varied from 20 °C to 70 °C. Additionally, a giant flexocoupling coefficient for bulk PVDF is obtained based on the experimental values of the flexoelectric coefficient and dielectric constant. This demonstrates the promising application of polymer polyvinyl fluoride in the field of sensing, energy harvesting, and among others.